Ecological immunity of human milk: Life history perspectives from the United States and Kenya. Issue 2 (20th August 2018) - Miller, Elizabeth M.
Abstract: Objectives: Previous research has established population variation in anti‐inflammatory immunological biomarkers in human milk. This immunity is potentially ecology‐dependent and may alter the life history trade‐off between growth and maintenance in infants. The current study has two aims: (1) to assess the ecological differences in milk immunity in two populations, one from the urban U.S. and one from rural Kenya; and (2) to test the hypothesis that milk immunity can affect infant growth indicators. Materials and Methods: Kenyan Ariaal ( n = 233) and U.S. ( n = 75) breastfeeding mother‐infant pairs participated in a cross‐sectional study at two separate field sites. Laboratory analysis was performed on milk for the anti‐inflammatory biomarkers TGF‐β2, sTNF‐αRI, sTNF‐αRII, and IL‐1ra using ELISA. Multiple imputation was used to extrapolate data below the limit of detection before multivariate analysis. Results: There were significant differences between U.S. and Kenyan mothers on all four milk biomarkers, with Kenyan mothers having significantly higher sTNF‐αRI and sTNF‐αRII and lower TGF‐β2 and IL‐1ra than U.S. mothers. U.S. mothers with higher milk TGF‐β2 and IL‐1ra have infants that are significantly longer and heavier for their age, while Kenyan mothers with higher sTNF‐αRI have significantly longer and heavier infants for their age, and those with higher TGF‐β2 have marginally significantly longer infants. Discussion: There were significant differences in ecological milk immunity between U.S. and Kenyan mothers. These differences potentially play a role in the growth of their infants. Further research in milk immunity should consider the possibility of shared maternal–infant life histories.